2012
DOI: 10.1590/s0085-56262012000400012
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Ephemeroptera (Insecta) of the Serra da Mantiqueira and Serra do Mar, southeastern Brazil

Abstract: ABSTRACT. Diversity of Ephemeroptera (Insecta) of the Serra da Mantiqueira and Serra do Mar, southeastern Brazil. The aim of this study was to inventory the mayfly fauna, based on nymphal and alate stages, in Serra da Mantiqueira and in Serra do Mar, São Paulo State, as well as to present information about habitats used by the genera. Nymphs were collected in several streams and mesohabitats with a Surber sampler and the winged stages with light attraction methods, entomological nets, and Malaise traps. In all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 27 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Observations along mountain ranges in south‐eastern Brazil have revealed that differences in climate, elevation and vegetational cover can impact habitat complexity and species composition (Cruz & Feio, 2007). The Serra do Mar mountain range is home to a greater number of species of plants (Marchiori et al, 2016; Pompeu et al, 2014), arthropods (Pinto‐da‐Rocha et al, 2005; Siegloch et al, 2012) and anurans (Malagoli et al, 2018; Silva et al, 2018) compared to the Serra da Mantiqueira mountain range. Anurans, known for their generalist and opportunistic feeding habits, prey on almost all kinds of invertebrates in their habitat (López et al, 2009; Rodrigues et al, 2004; Solé et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Observations along mountain ranges in south‐eastern Brazil have revealed that differences in climate, elevation and vegetational cover can impact habitat complexity and species composition (Cruz & Feio, 2007). The Serra do Mar mountain range is home to a greater number of species of plants (Marchiori et al, 2016; Pompeu et al, 2014), arthropods (Pinto‐da‐Rocha et al, 2005; Siegloch et al, 2012) and anurans (Malagoli et al, 2018; Silva et al, 2018) compared to the Serra da Mantiqueira mountain range. Anurans, known for their generalist and opportunistic feeding habits, prey on almost all kinds of invertebrates in their habitat (López et al, 2009; Rodrigues et al, 2004; Solé et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Köppen (1948) assumed that the regional climate can be classified as Cwa, characterized by warm, wet summers and dry winters. The average minimum temperature is 10.6 °C, the maximum of 26.1 °C (Martins, 2010) and the average annual rainfall of 2,200 mm with the wettest months being December, January and February (Siegloch et al 2012). We selected four specific plant traits to compose our functional analysis: Leaf Nitrate reductase activity (NRA), arginine (ARG) and glutamine (GLN) in the xylem sap based on nitrogen use model (Aidar et al 2003) and Specific Leaf Area (SLA), a very common and widely used in plant traits approaches, which represents the light-intercepting area of a leaf per unit dry mass, related to net assimilation rate (Reich et al 1997) and plant relative growth rate (RGR: Reich et al 1997, Poorter & Jong 1999) (Table 3).…”
Section: Study Sitesmentioning
confidence: 99%